2019
DOI: 10.4153/cmb-2018-016-4
|View full text |Cite
|
Sign up to set email alerts
|

Monoidal Categories, 2-Traces, and Cyclic Cohomology

Abstract: In this paper we show that to a unital associative algebra object (resp. co-unital co-associative co-algebra object) of any abelian monoidal category C endowed with a symmetric 2-trace, one can attach a cyclic (resp. cocyclic) module, and therefore speak of the cyclic (co)homology of the (co)algebra "with coefficients in F ". We observe that if M is a C-bimodule category equipped with a stable central pair then C acquires a symmetric 2-trace. The dual notions of symmetric 2-contratraces and stable central cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Remark 2.7. The current approach to general stability of aYD modules, via stability of aYD contramodules (implicitly as in [9] or explicitly as in Definition 2.5), may seem unsatisfactory but it is the only way in general. In particular situations one may do better.…”
Section: The Module Variant Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 2.7. The current approach to general stability of aYD modules, via stability of aYD contramodules (implicitly as in [9] or explicitly as in Definition 2.5), may seem unsatisfactory but it is the only way in general. In particular situations one may do better.…”
Section: The Module Variant Modificationsmentioning
confidence: 99%
“…The resulting categories are isomorphic to each other, and in turn isomorphic to the center of a certain bimodule category. As in [9] consider a monoidal functor # : H M → H M, taking a left H-module M to M # , where M # is the same as M as a k-vector space but the module structure is modified by S 2…”
Section: Recalling Quasi-hopf Algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach to this problem is afforded by [12] where it is shown that the monoidalcategorical point of view provides a way to extract the necessary formulas from a conceptual model of the situation. It is demonstrated that indeed one obtains the usual definitions in the Hopf algebra case.…”
Section: Introductionmentioning
confidence: 99%
“…The paper is organized as follows. In Section 2 we discuss some generalities as in [12,22] concerning a conceptual definition of contramodule coefficients for a suitable monoidal category. A new phenomenon that arises in this paper is the difficulty of proving that a certain natural map is an isomorphism.…”
Section: Introductionmentioning
confidence: 99%